Student’s performance factor review: engineering science course context - Rosmida Binti Ab Gahani; Najah Binti Mohd Nawi (Education and Social Sciences Review, 2020)
A mastery in Engineering Science Course is closely related to the physics subjects in schooling which involve problem solving techniques including mathematical skills. Engineering Science Course is considered difficult and complicated that need to be understood since there are many concepts to understand, especially for students who do not take science courses in school. Mastery of a course is closely linked to academic achievement that has a great impact on student achievement. Thus, a study was conducted to identify factors that influence student’s performance in the Engineering Science Course at Politeknik Sultan Mizan Zainal Abidin (PSMZA). A total of 179 respondents from four departments; Department of Civil Engineering (JKA), Department of Electrical Engineering (JKE), Department of Mechanical Engineering (JKM) and Department of Mathematical Science & Computer (JMSK) were involved in this study. The analysis of the study was done using descriptive statistics, T-test and Pearson Correlation using Statistical Package for Social Science (SPSS) version 23. Analysis of the result shows that environment was the main driving force with the mean value of 4.31 being the highest score compared to existing knowledge factors, interests, attitudes, lecturers and peers. T-test analysis also found that there was a significant relationship between attitude and gender differences. Pearson Correlation’s analysis found that the relationship between lecturers and interests was average and significant. While peers, environment and interest were strongly related, but significant. It is hoped that the findings of this study will help to provide an overview of the factors that influence student performance in the Engineering Science Course at PSMZA. This will also help JMSK to take preventive measures and improve all aspects of its efforts to improve student performance in the Engineering Science Course at PSMZA.